Means of Expressing Participant in English and Lithuanian Texts - Буйткене, Янина (Kalbotyra, 1987)
Participant line as well as Event line can be seen as the backbone of a text in any language. The identification of the participant is realized by various lexical devices in English and Lithuanian texts. They include: reiteration of the same word, reiteration of a synonym or near-synonym, reiteration of an antonym, reiteration of a superordinate, reiteration of words related as part to whole, etc.